Parasitism and grooming behavior of a natural white-tailed deer population in Alabama. Issue 3 (4th May 2017) - Heine, Kyle B.; DeVries, Philip J.; Penz, Carla M.
Abstract : We assessed responses in grooming behavior to ectoparasite densities in naturally occurring white-tailed deer ( Odocoileus virginianus ) in southwest Alabama, and tested predictions of the stimulus-driven and programmed grooming models with respect to intraspecific body size and vigilance. Stimulus-driven grooming predicts greater tick densities would lead to an increase in grooming, whereas the programmed model predicts a higher rate of grooming would decrease tick densities. Within the programmed model, smaller individuals are predicted to groom more and host fewer ticks, and, due to increased vigilance, breeding males will groom less than females and bachelor males, and thus host more ticks during the rut. We used generalized linear models to determine males had a higher average tick density than females and exhibited complete separation of tick parasitism between non-rutting and rutting periods. Our results support the stimulus-driven grooming model as both fawns and yearlings had significantly higher deer ked and combined deer ked/tick densities than adults. We used Mann–Whitney U tests to conclude fawns oral groomed at a significantly higher rate than adults, even in the absence of allogrooming. Programmed and stimulus-driven grooming were not mutually exclusive, but rather ectoparasite and host dependent. Although individuals observed grooming were analyzed separately from harvested individuals, we infer that heavy deer ked densities may lead to higher grooming rates. We suggest white-tailed deer grooming for ticks should be considered within an evolutionary framework, and grooming for deer keds should be viewed as a proximate response to agitation. This is the first study to show that deer keds may have a greater influence in overall grooming behavior of deer than do ticks. We recommend that future studies should consider other ectoparasites along with ticks to understand their effects on grooming behavior in dimorphic terrestrial mammals.